Climate change awareness of gen z: the influence of frame and jargon on online news - Ariestya, Angga; Paramitha, Gracia; Elmada, Maria Advenita Gita (Faculty of Communications Science, Dr. Soetomo University, 2022)
This study seeks to know how climate change frames and jargon in online news influence Gen Z’s awareness. It is important since only a few studies on climate change communication focus on Gen Z. The research took the quantitative within-subject experimental method to college students as participants (N=110). Participants were divided into an experimental and control group and manipulated by customised online news containing frames and jargon about climate change. The finding is that the climate change frame on the online news influences Gen Z’s awareness, while jargon does not. The awareness is higher when Gen-Z was given an uncertainty-risk frame than an economic cost-benefit frame. Despite Gen Z being aware of climate change, a correlation between cognitive and conative awareness is arguably low. The internal factor (less role model) and external factor (less policy involvement) could be the factors of low conative awareness.